Pengaruh Gaya Kepemimpinan dan Kompensasi Terhadap Semangat Kerja Pegawai Honorer Puskesmas Sioban, Kecamatan Sipora Selatan, Kabupaten Kepulauan Mentawai - Hartawan, Wahyu Kurnia; Salfadri, Salfadri; Sunreni, Sunreni (Ekasakti Matua Jurnal Manajemen, 2023)
The results of this study aim to examine and analyze the Effect of Leadership and Compensation Style on the Work Spirit of the Honorary Employees of the Sioban Health Center, Sipora Selatan District, Mentawai Islands District. Where Variable X1 Is Leadership Style, X2 Compensation, Dependent Variable Is Morale. This study uses a classic assumption test which consists of a normality test, a multi-priority test, a heroskadisity test and a multiple regression test, a t test and an F test. The results of the Study of Leadership Style Variable have a positive and significant effect on morale, Compensation has a positive and significant effect on morale, the variables of leadership style and compensation simultaneously or simultaneously have a significant and significant effect on morale. The contribution of Leadership Style and Compensation to the Spirit of Work is 76.60% while the remaining 23.40% is influenced by other variables outside this study such as motivation, competence and others.